The Cambridge handbook of pragmatics - Allan, Keith, 1943-; Jaszczolt, Katarzyna (Cambridge : Cambridge University Press, 2012)
'Pragmatics is the study of human communication: the choices speakers make to express their intended meaning and the kinds of inferences that hearers draw from an utterance in the context of its use. This Handbook surveys pragmatics from different perspectives, presenting the main theories in pragmatic research, incorporating seminal research as well as cutting-edge solutions. It addresses questions of rational and empirical research methods, what counts as an adequate and successful pragmatic theory, and how to go about answering problems raised in pragmatic theory. In the fast-developing field of pragmatics, this Handbook fills the gap in the market for a one-stop resource to the wide scope of today's research and the intricacy of the many theoretical debates. It is an authoritative guide for graduate students and researchers with its focus on the areas and theories that will mark progress in pragmatic research in the future'--
'Pragmatics is the study of human communication: the choices speakers make to express their intended meaning and the kinds of inferences that hearers draw from an utterance in the context of its use. This Handbook surveys pragmatics from different erspectives, presenting the main theories in pragmatic research, incorporating seminal research as well as cutting-edge solutions. It addresses questions of rational and empirical research methods, what counts as an adequate and successful pragmatic theory, and how to go about answering problems raised in pragmatic theory. In the fast-developing field of pragmatics, this Handbook fills the gap in themarket for a one-stop resource to the wide scope of today's research and the intricacy of the many theoretical debates. It is an authoritative guide for graduate students and researchers with its focus on the areas and theories that will mark progress in pragmatic research in the future'--
Machine generated contents note: 1. Introduction: pragmatic objects and pragmatic methods Kasia M. Jaszczolt and Keith Allan; Part I. Problems and Theories: 2. Research paradigms in pragmatics Mira Ariel; 3. Saying, meaning, and implicating Kent Bach; 4. Implying and inferring Laurence R. Horn; 5. Speaker intentions and intentionality Michael Haugh and Kasia M. Jaszczolt; 6. Context and content: pragmatics in two-dimensional semantics Berit Brogaard; 7. Contextualism: some varieties Fran's Recanati; 8. The psychology of utterance processing: context vs. salience Rachel Giora; 9. Sentences, utterances, and speech acts Mikhail Kissine; 10. Pragmatics in update semantics Henk Zeevat; 11. The normative dimension of discourse Jaroslav Peregrin; 12. Pragmatics in the (English) lexicon Keith Allan; 13. Conversational interaction Michael Haugh; 14. Empirical investigations and pragmatic theorising Napoleon Katsos; Part II. Phenomena and Applications: 15. Referring in discourse Arthur Sullivan; 16. Propositional attitude reports: pragmatic aspects Kasia M. Jaszczolt; 17. Presupposition and accommodation in discourse Rob van der Sandt; 18. Negation Jay David Atlas; 19. Connectives Caterina Mauri and Johan van der Auwera; 20. Spatial reference in discourse Luna Filipovi{u28FB} 21. Temporal reference in discourse Louis de Saussure; 22. Textual coherence as a pragmatic phenomenon Anita Fetzer; 23. Metaphor and the literal/nonliteral distinction Robyn Carston; Part III. Interfaces and the Delimitation of Pragmatics: 24. Pragmatics in the history of linguistic thought Andreas H. Jucker; 25. Semantics without pragmatics? Emma Borg; 26. The syntax/pragmatics interface Ruth Kempson; 27. Pragmatics and language change Elizabeth Closs Traugott; 28. Pragmatics and prosody Tim Wharton; 29. Pragmatics and information structure Jeanette K. Gundel; 30. Sociopragmatics and cross-cultural and intercultural studies Istvan Kecskes; 31. Politeness and pragmatics Marina Terkourafi.
Includes bibliographical references (p. 678-757) and index.
Keywords: Pragmatics